Efficacy of Prophylactic Fluconazole Therapy in Decreasing the Incidence of Candida Infections in Extremely Low Birth Weight Preterm Infants - Cetinkaya, Merih; Ercan, Tugba Erener; Saglam, Ozge Kurum; Buyukkale, Gokhan; Kavuncuoglu, Sultan; Mete, Fatih (American Journal of Perinatology, 2014)
Objective Systemic fungal infections are major causes of morbidity and mortality, and are associated with significant neurodevelopmental impairment in premature infants. Our objective was to evaluate the efficacy of fluconazole prophylaxis in prevention of systemic fungal infections among preterm infants.Study Design This observational pre-post cohort study was performed in preterm infants with a birth weight of < 1,000 g who were given prophylactic fluconazole starting on the first postnatal day at a dose of 3 mg/kg twice a week. These infants were compared with preterm infants who were not given prophylaxis.Results Prophylaxis group consisted of 90 infants and control group consisted of 107 infants. Systemic fungal infection was observed in five patients (4.7%) in the control group while no fungal infection was detected in the prophylaxis group (p = 0.03). There were no significant differences between two groups in terms of demographic features, maternal and neonatal risk factors, and all-cause mortality rates. No adverse reactions were seen during the prophylaxis period.Conclusions We suggest that intravenous fluconazole prophylaxis at a dose of 3 mg/kg twice a week is a safe and effective strategy for decreasing systemic fungal infections even in neonatal intensive care units with low rates of invasive Candida infection.
Keywords: Candida; fluconazole; infection; preterm; prophylaxis